A new Celtiberian inscription on stone from El Pueyo de Belchite (Zaragoza) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A new Celtiberian inscription on stone has been found in the archaeological site of El Pueyo (Belchite, Zaragoza). This paper provides an edition and a study of this inscription.
Keywords: Celtiberian epigraphy; Inscription on stone; Archaeology; El Pueyo; Belchite; Zaragoza